(untitled) (Journal of Engineering, 2006)
This paper brings together random field generation and finite element technique to model steady state seepage through two dimensional soil domain in which the hydraulic conductivity is randomly distributed in space. The analysis treats the hydraulic conductivity as a spatially random property with specified mean, variance and spatial correlation length. The results of the combined model used in an optimization procedure to obtain the optimum dimension of the hydraulic structure seepage control techniques.